2022
DOI: 10.1016/j.heliyon.2021.e08710
|View full text |Cite
|
Sign up to set email alerts
|

Are job satisfaction and role breadth self-efficacy the links to proactive work behavior?

Abstract: This research is based on a phenomenon that occurs in State Detention Centers in Indonesia. It attempts to test the relation among proactive personality (PP), proactive work behavior (PWB), job satisfaction (JS) and role breadth self-efficacy (RBSE) variables. With a quantitative approach using AMOS, this study took data from 455 respondents from Detention Centers in Indonesia. The results show that PP, JS and RBSE have direct effect on PWB. Further findings will be discussed. The results are expected to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Self-management positively and significantly affects PWB proactive work behavior in the millennial generation at PT Satria Parang Tritis. It is in line with previous research, which concluded that selfmanagement positively and significantly influences proactive work behavior (Syamsudin et al, 2022;Zahra, 2019). In line with previous research, self-management positively and significantly affects proactive work behavior (Damayanti & Ratnaningsih, 2020;M.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Self-management positively and significantly affects PWB proactive work behavior in the millennial generation at PT Satria Parang Tritis. It is in line with previous research, which concluded that selfmanagement positively and significantly influences proactive work behavior (Syamsudin et al, 2022;Zahra, 2019). In line with previous research, self-management positively and significantly affects proactive work behavior (Damayanti & Ratnaningsih, 2020;M.…”
Section: Discussionsupporting
confidence: 92%
“…Several factors can influence proactive work behavior: protean career attitude, passion for work, and self-management (Syamsudin et al, 2022;Tsai, 2022). The aspect of a protean career attitude is one of the factors that can influence proactive work behavior, where individuals who have a protean career attitude tend to take action to be able to influence their environment and will focus more on pursuing opportunities in terms of self-improvement that is flexible in choosing their life path (Ingarianti et al, 2020;Rizka, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, facility care employees are dissatisfied with the supervisor's ability to provide feedback, including giving awards to employees. which has performed well (Syamsudin et al, 2022;Lim & Loo, 2003;Darvishmotevali & Ali, 2020).…”
Section: Description Of Job Satisfactionmentioning
confidence: 97%
“…Buyers will buy a product if it feels right, therefore the product must be adjusted to the wants or needs of the buyer for product marketing to be successful. In other words, product creation is better oriented to market desires or consumer tastes (Syamsudin et al, 2022). According to Armstrong et al (2014) is "anything that can be offered to a market for attention, purchase, use, or consumption that might satisfy a want or need".…”
Section: Product Qualitymentioning
confidence: 99%